Congenital digital flexural deformity (knuckling): Epidemiology, the association of trace elements and surgical treatment in neonatal bovine calves (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: This study aimed to investigate the prevalence and pattern of congenital flexural deformity (knuckling), to identify the association between trace elements and vitamins with the deformity, and to apply different surgical techniques for correcting this congenital malformation in newborn bovine calves. Materials and Methods: The study was implemented on 17 newborn calves with carpal (knee) and fetlock (foot) knuckling presented to the Veterinary Teaching Hospital of Bangladesh Agricultural University, Mymensingh, from January to December 2020. The serum biochemical alterations and clinical outcomes were assessed on days 0 and 21 following surgery. Two surgical methods: tendon transection and tendon elongation by Z-tenotomy, were performed for surgical restoration. Results: We found that knuckling comprised 12% of the total congenitally malformed calves. The male calves had a higher prevalence (52%, n = 9) and the same in the winter season (65%, n = 11). The majority of the knuckling was bilateral types (88%, n = 15), involving the carpal joint (82%, n = 14) and moderately angulated (59%, n = 10). The serum level of magnesium, iron, vitamin D, and zinc were significantly (p < 0.05) changed from the pre-surgical stage to the stage of non-lameness after surgery. The disorder was surgically treated by tendon transection or tendon elongation procedure and had a good prognosis. Conclusion: The current study concluded that the development of knuckling in calves might be related to a deficiency/excess of specific minerals and vitamins and that it can be effectively corrected by surgical intervention; however, early diagnosis and the use of proper surgical techniques are crucial for improving the prognosis.J. Adv. Vet. Anim. Res., 10(1): 88–95, March 2023http://doi.org/10.5455/javar.2023.j656